UPAYA PENINGKATAN KEMAMPUAN MENARI TARI TOPENG GUNUNGSARI PADA MAHASISWA JURUSAN PENDIDIKAN SENI TARI DENGAN PENDEKATAN APRESIASI SENI DAN LATIHAN SECARA RUTIN - herlinah, herlinah (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; .MsoPapDefault mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Abstract The research was purposed to make efforts to improve Dance Education Department student dancing abilities of Topeng Gunungsari Dance by Art Appreciation method and practiced routinely. The research used design models which were developed by Kemmis & Mc. Taggart consisted of four components included: planning, action, observation, and reflection. The researchers planned and established action types which would be done, that were: student practiced together by masks, and watched a Topeng Gunungsari Dance performance by video recording routinely. The research result of dance studying was that by the practiced and watched a Topeng Gunungsari Dance video recording routinely could improve dancing abilities of Topeng Gunungsari dance. Key words: dancing ability, art appreciation, routine practice.